Ocular complications after external-beam irradiation – a literature overview - Ziółkowska, Ewa; Zarzycka, Małgorzata; Meller, Aleksandra; Wiśniewski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2009)
Radiotherapy is one of the treatment methods applied to patients suffering from head and neck cancer. The efficiency of this method is comparable to surgery, yet it allows one to save the organ and avoid its permanent deformation. In the case of radiation not only the tumour is influenced but the surrounding, normal structures as well. Radiation causes deformation of normal structures as early or side effects. The aim of this study is to present plausible ocular complications after external-beam irradiation of head and neck cancer, such as radiation-induced cataract, radiation retinopathy, dry-eye syndrome or radiation neuropathy. By the use of basic principles of radiotherapy planning we can avoid or minimize possible ocular complications occurring after irradiation. The treatment of ocular complications is difficult and very often does not give the expected outcome. Therefore, in such cases in order to restore vision surgery is required. This study shows that radiotherapy can be helpful but can increase the risk of occurrence of some ocular complications.